FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH DALAM PENGGUNAAN APBD KABUPATEN SORONG SELATAN - Kondologit, Yulian; Tuarita, Juniyanti (P3M Politeknik Negeri Ambon, 2023)
The problems in this study is the delay in submitting material on the Regional Budget Draft to be discussed in the Budget Session. The purpose of this study is to determine and analyze the implementation of the Regional Budget of South Sorong Regency. As we all know that there are three functions of the Regional People's Representative Council, namely legislation, budget, and supervision. This study used the Qualitative Descriptive Research model. There are two sources of data in this study, namely primary data and secondary data. Primary data obtained by interviewing informants. While secondary data sources are obtained with observations and documentation.The results showed that in terms of the results of the implementation of the legislative function has been carried out properly and in accordance with Law Number 23 of 2014. This is intended because the Regional People's Representative Council can complete each draft of existing Regional Regulations. The implementation of the budget function has been carried out well through political lobbying, both among fellow legislators and between legislators and executives. The implementation of the supervisory function has been carried out well. This is evidenced by the participation of board members in overseeing all Local Government policy programs. The suggestion in this study is that the Regional People's Representative Council of South Sorong Regency should pay attention to environmental, economic, health, social conditions in reviewing a draft Regional Regulation so that the policies decided are in accordance with the expectations of the community so that they become satisfied. The Regional Representative Council of South Sorong Regency should be more careful in the agenda of discussing the Regional Revenue and Expenditure Budget to be in accordance with the financial condition of the Regional Government. We recommend that the Regional People's Representative Council of South Sorong Regency be more active in carrying out its supervisory function. One way is to monitor and evaluate the management of the Regional Budget of South Sorong Regency.Keywords: Function, Regional People's Representative Council, Regional Revenue and Expenditure Budget.